Sanctions, Perceptions, and Crime: Implications for Criminal Deterrence - Apel, Robert (Journal of quantitative criminology, 2013)
Objectives A survey of empirical research concerning the determinants of an individual’s perceptions of the risk of formal sanctions as a consequence of criminal behavior. The specific questions considered are: (1) How accurate is people’s knowledge about criminal sanctions? (2) How do people acquire and modify their subjective probabilities of punishment risk? (3) How do individuals act on their risk perceptions in specific criminal contexts? Methods Three broad classes of extant studies are reviewed. The first is the relationship between objective sanctions, sanction enforcement, and risk perceptions—research that includes calibration studies and correlational studies. The second is the relationship between punishment experiences (personal and vicarious) and change in risk perceptions, in particular, research that relies on formal models of Bayesian learning. The third is the responsiveness of would-be offenders to immediate environmental cues—a varied empirical tradition that encompasses vignette research, offender interviews, process tracing, and laboratory studies. Results First, research concerning the accuracy of risk perceptions suggests that the average citizen does a reasonable job of knowing what criminal penalties are statutorily allowed, but does a quite poor job of estimating the probability and magnitude of the penalties. On the other hand, studies which inquire about more common offenses (alcohol and marijuana use) from more crime-prone populations (young people, offenders) reveal that perceptions are consistently better calibrated to actual punishments. Second, research on perceptual updating indicates that personal experiences and, to a lesser degree, vicarious experiences with crime and punishment are salient determinants of changes in risk perceptions. Specifically, individuals who commit crime and successfully avoid arrest tend to lower their subjective probability of apprehension. Third, research on the situational context of crime decision making reveals that risk perceptions are highly malleable to proximal influences which include, but are not limited to, objective sanction risk. Situational risk perceptions appear to be particularly strongly influenced by substance use, peer presence, and arousal level. Conclusions The perceptual deterrence tradition is theoretically rich, and has been renewed in the last decade by creative empirical tests from a variety of social scientific disciplines. Many knowledge gaps and limitations remain, and ensuing research should assign high priority to such considerations as sampling strategies and the measurement of risk perceptions.